A STUDY OF URBAN LIVEABILITY IN A CITY AND A SUBURBAN. CASE STUDY: KUALA LUMPUR AND PUNCAK ALAM, MALAYSIA. - Hoon Leh, Oliver Ling; Abdul Aziz, Muhammad Hanif; Mohd Mahbot, Norseha; Marzukhi, Marlyana Azyyati; Nasrudin, Na'asah (Journal of Surveying, Construction and Property, 2020)
Urban always being the main catalyst of growth in most of the countries. However, due to the high concentration of population, urbans encounter various challenges, i.e. environmental degradation, social unhealthiness, low sense of security, unhealthy lifestyle and traffic congestion. These phenomenon affect the liveability of urban dwellers. Liveability is affected by physical environmental and social aspects. A liveability study had been carried out in Kuala Lumpur city (with Mandy Villa as the study area) and a suburban (Puncak Alam). This paper is prepared with the aim to analyse the liveability of the residents in these areas and the relationship with the physical and social aspects. With a questionnaire survey, the respondents with diverse social and demographic background were mostly felt that the study areas were liveable. Relationship analysis via correlation tests showed that some of the physical aspects and most of the social aspects were positively and significantly related to the liveability level. With the research findings, urban managers, planners, private company and public agencies can come out with better strategies to improve the urban liveability. Nevertheless, more studies should be carried out in future for different locality for a better understanding of the urban liveability and the determining factors.